Biochemical and nutritional aspects of vulvovaginitis: aspectos dietéticos e bioquímicos - Linhares, I.M.; Miranda, S.D.; Vergolino, R.V.D; Caetano, M.E.; Peixoto, S. (Brazilian Journal of Sexually Transmitted Diseases, 1998)
Vulvovaginitis, a malady of diverse pathologies which affect the lower fcmale genital tract, has been, since Hypocrites and Soranus, an important manifestation of disorders whith are potentialy scrious to women's genital and general well being health. Various papers have strongly emphasized the microbiological aspects of these diseases. However, little has been done to avoid this p:roblem regarding othcr factors such as diet and a non-conventional approach. This paper focuses on the biochemical and nutritional aspects of the normal vaginal conten ts, describing the mosl frequent findings, as well as the possible interaction with the microflora. Mechanism of protection or those that lead to vaginal discharge are pointed out, stressing the importance ofthe aminoacids and the immunoglobulin, secreted mainJy by local vaginal mucous. The knowledge of these aspects can be an important factor for the gynecologist to be able to establish a co-relation between clinical and laboratorial findings and consequently explain the pathophysiologicaJ actions in certain cases, fundamental basis for perfect diagnosis and treatment.